2002
DOI: 10.1080/1025389021000010558
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Repetitive Hypoglycemia on Neuroendocrine Response and Brain Tyrosine Hydroxylase Activity in the Rat

Abstract: Effects of repetitive hypoglycemia on neuroendocrine response and brain tyrosine hydroxylase activity in the rat. Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.Downloaded from the University of Groningen/UMCG research database (Pure): http://www.rug.nl/research/portal. For technical reasons the number of authors shown on this cover page is limited to 10 maximum. Hypoglycemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…All animals underwent bilateral implantation of intravenous (IV) silastic catheters under ketamine/xylazine anesthesia (60 mg/kg ketamine (KetaFlo™, Abbott Laboratories, Chicago, IL), 7.8 mg/kg xylazine (Xyla-Ject ® , Phoenix Pharmaceutical, St. Joseph, MO)) as in our previous studies (Figlewicz et al, 2002). For each rat, the right jugular vein and the left submaxilary vein were catheterized.…”
Section: Surgerymentioning
confidence: 99%
“…All animals underwent bilateral implantation of intravenous (IV) silastic catheters under ketamine/xylazine anesthesia (60 mg/kg ketamine (KetaFlo™, Abbott Laboratories, Chicago, IL), 7.8 mg/kg xylazine (Xyla-Ject ® , Phoenix Pharmaceutical, St. Joseph, MO)) as in our previous studies (Figlewicz et al, 2002). For each rat, the right jugular vein and the left submaxilary vein were catheterized.…”
Section: Surgerymentioning
confidence: 99%
“…Among these, and of critical importance to the brain, is the regulation of glucose. Glucose is the primary and essential energy source for the brain, and glucose deprivation, either through natural or pharmacologic means, elicits feeding and other counterregulatory responses such as corticosterone and glucagon secretion (Borg et al, 1995; Ritter et al, 2001, 2003; Figlewicz et al, 2002). Studies performed in coronal sections have demonstrated neurophysio-logic responses to acute changes in glucose using patch clamp electrophysiology of the cNST (Wan and Browning, 2008) and DMN (Balfour et al, 2006; Wan and Browning, 2008), and demonstrate how low glucose effects individual neurons.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have performed i.p administration of insulin to induce antecedent hypoglycaemia [30, 33, 34, 38, 61]. Although the most preferred route of administration in many studies is the i.v route [35, 36, 39, 40, 4244] (see Table 2), some researchers have used a combination of i.p and i.v or s.c and i.v with the i.p or s.c injections used to induce antecedent hypoglycaemia and the i.v administration or continuous i.v infusion used to produce the subsequent hypoglycaemic episode [30, 31, 33, 34, 37, 41]. Intravenous infusions have the advantage of achieving the desired hypoglycaemia levels relatively quickly, but it requires the animals to be surgically fitted with venous catheters to enable researchers to perform repeated i.v administration and thus requires specialised skills which could be challenging.…”
Section: Reproducing the Haaf Phenomenon In Rodentsmentioning
confidence: 99%
“…Also, administration of high insulin concentrations may not necessarily reproduce the phenomenon more successfully. For example, Figlewicz et al [44] and Paranjape and Briski [29] who administered 6.75 U/kg and 12 U/kg insulin, respectively, to induce both antecedent and subsequent hypoglycaemia were unable to achieve a significant reduction in plasma adrenaline response to subsequent hypoglycaemic episode. However, these two studies have not reported the levels of hypoglycaemia achieved with these insulin concentrations.…”
Section: Reproducing the Haaf Phenomenon In Rodentsmentioning
confidence: 99%